Influence of Extension Education on Adoption of Forestry Conservation Practices in South Eastern Nigeria (2016)
Extension education programmes were observed to have positive impact on different sectors of the economy in developed society. However, forestry and other natural resources sub-sectors in Africa and by extension, Nigeria still lag behind and its growth and development is nothing compared with other sub-sectors. This paper reports the influence of conservation and extension education programmes on the adoption of conservation practices by households in Anambra Sate, south-eastern Nigeria with the view to determining the impact of education on natural resources conservation and development. The study was targeted at household heads across selected communities in Aguata agricultural zone of Anambra State, Nigeria, using, village grouping meetings and two sets of structured and open ended questionnaire. Information was sought on respondents’ participation levels in extension education and relative adoption rates of household level conservation practices. Data obtained were analysed using descriptive and inferential statistics. Awareness and education programmes considered include governmental non-governmental conservation programmes earlier executed in the study area, Anambra State Agricultural Development Programme (ADP) extension services as well as conservation/forestry extension training and education provided specifically for the study being reported. Respondents’ consent to participating in identified conservation programmes in the stud area was highest (91.6%) for conservation of trees that are located away from their residence. This was followed by training in poultry and wildlife domestication (90.4%). The least interest was expressed for arable and tree crop mix on the same land (10.8%). Also, planting of palm and exotic trees in the study area were found to have stemmed from the households’ access to government extension services (X2=7.3 and 4.6; df = 2) and the research organized through forestry extension education/awareness training (X2= 15.1 and 9.7; df = 1). Respondents’ participation in past conservation education programmes has impacted on poultry and wildlife domestication (X2= 8.16; df = 2), agri-silviculture (X2 = 12.8; df =2) and land management practice (X2 = 4.8; df =2) activities in the study area. Village level discussions showed that respondents’ would readily adopt innovations, which are compatible with their traditional agricultural practices although such adoption will depend on the frequency of their exposure to innovative programmes. It was also found that Local conservation programmes and activities especially for the informal sector of the economy can be made more robust and better executed periodically and jointly too by public and private organizations and stakeholders.